Differences In The Level of Work Anxiety on Contract Teachers - Yoan Mariane Fanggi; M. K. P. Abdi Keraf; Indra Kiling (Universitas Nusa Cendana, 2021)
Anxiety is an emotional condition that has the characteristics of physiological, unpleasant tense feelings, and a feeling of worryng that something bad will happen. The things that are worried about health, social relationships, and career. Everyone must experience anxiety, no exception for someone who works as a contract teacher. Uncertainty about their future status and the demands of life are becoming some of the main factors causing anxiety. This study aims to determine the differences in the level of work anxiety on the contract teachers of SMA Seminari St. Rafael Kupang and SMA Negeri 3 Kupang city. This type of research is about quantitative research. The sample size is 45 contract teachers who are willing to fill out the questionnaire scale. The variables studied were tested using the independent sample t test to determine the differences in the level of work anxiety on the contract teachers of the Seminary St. High School Rafael Kupang and SMA Negeri 3 Kupang City. The test results of the Independent sample T-test stated anxiety between the contract teachers of St. Seminary Senior High School Rafael Kupang and SMA Negeri 3 Kupang city, there is no significant difference between. This is obtained from the sig (1-tailed) result of (0.086) (p> 0.05) so that H0 is rejected, meaning that there is no significant difference in work anxiety between the contract teachers of the Seminary St. High School. Rafael Kupang and SMA Negeri 3 Kupang City. Therefore, there is no difference in job anxiety between public and private contract teachers.